Improvements on Solution-Based IGZO TFTs Optoelectronic Properties - Luo, Haoci (Transactions on Computer Science and Intelligent Systems Research, 2025)
Indium gallium zinc oxide (IGZO) gained significant attention in the semiconductor and display industries due to its high carrier mobility, excellent flexibility, and superior transparency. These features meet the growing demand for higher resolution and foldable displays. Solution-based IGZO thin-film transistors (TFTs) have demonstrated great potential for reducing production costs and enhancing the optoelectronic performance of display devices. However, several challenges remain, including poor uniformity caused by uneven precursor deposition, high defect state density, which limit the carrier mobility and current controlling capability of the transistor. This paper first introduces the fundamental principles and parameters used to quantify the electric performance of the TFTs. Then ummarizes current optimization strategies such as annealing temperature, metal doping, and substrate material selection, based on the aforementioned performance parameters. Additionally, the effect of embedding an indium zinc oxide (IZO) layer into the Hf-doped IGZO film is discussed, aiming to increase free electron concentration and reduce oxygen defect density. finally, the paper proposes future optimization directions, including the design of multiphase semiconductor structures and the introduction of electromagnetic wave irradiation between pre- and post-annealing steps. These strategies are expected to enable the fabrication of IGZO TFTs with enhanced electrical performance and greater commercial viability.